Taking Butler Elsewhere: Performativities, Spatialities and Subjectivities - Gregson, Nicky; Rose, Gillian (Environment and planning. D, Society & space, 2000)
This paper is concerned with exploring the potential of performance and performativity as conceptual tools for a critical human geography. We begin by emphasising the importance of recognising the different ways in which performance can be theorised, and their very different critical effects. We then argue that, although the geographical literature is apparently characterised by two contrasting discussions of performance (those of Goffman and of Butler), these accounts form a consensus around Goffman. By contrast, and along with Butler, we maintain that performance is subsumed within and must always be connected to performativity—that is, to the citational practices which produce and subvert discourse and knowledge, and which at the same time enable and discipline subjects and their performances. But we also take Butler elsewhere, arguing that spaces too need to be thought of as performative, and that more needs to be made of the complexity and instability of performances and performed spaces. To illustrate our general arguments, but also to show how they work out rather differently in the specificities of particular social practices, we draw on two very different pieces of research which we have separately been involved in: a study of community arts workers and projects in Edinburgh and another on car-boot sales as alternative spaces of consumption. We conclude the paper by arguing for the necessity of extending our arguments to encompass academic performances and performativity, reflecting on our own production, both through particular academic performances of our respective research projects and this paper.